2015
DOI: 10.1007/s00261-015-0430-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasonography in the imaging of body packers comparison with CT: a prospective study

Abstract: Ultrasonography was found to have a high sensitivity but a low specificity in suspected cases. A negative ultrasonography cannot rule out the diagnosis of body packing. However, it may be preferred as the initial imaging method or for follow-up of suspected cases as a radiation-free, easy-to-use, and inexpensive technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…A negative ultrasonography cannot rule out the diagnosis of body packing. However, it may be preferred as the initial imaging method or for follow-up of suspected cases as a radiation-free, easy-to-use, and inexpensive technique [71]. Magnetic resonance imaging (MRI) is rarely used as first-line emergency modality because of its high costs and limited availability.…”
Section: Ultrasound and Mrimentioning
confidence: 99%
“…A negative ultrasonography cannot rule out the diagnosis of body packing. However, it may be preferred as the initial imaging method or for follow-up of suspected cases as a radiation-free, easy-to-use, and inexpensive technique [71]. Magnetic resonance imaging (MRI) is rarely used as first-line emergency modality because of its high costs and limited availability.…”
Section: Ultrasound and Mrimentioning
confidence: 99%
“…In addition, a negative exam does not exclude intracorporal packs that may be disguised by superimposing structures, for example, gas. 25,30 In this case, death did not occur within minutes based on the amount of ineffective metabolites of cocaine. The decompositional changes and the musculature sample obtained instead of blood did not allow further precision.…”
Section: Discussionmentioning
confidence: 78%
“…Although ultrasonography has been used in the diagnostic assessment of body packers for years, the literature knowledge of this subject is still limited. 23,[30][31][32] Ultrasonography can be used as the first choice in the detection of intestinal obstruction secondary to packages and intra-abdominal free fluid. 12 Furthermore, it has been reported that an intravaginal package was detected in a suspect using sonography.…”
Section: Ultrasonographymentioning
confidence: 99%
“…The authors reported that abdominal ultrasonography was a valuable method with results available within minutes, one that could be used as a screening method to detect suspected cases of body packing at airports. 30 Cengel et al 32 in a recent study, in which ultrasonography and CT were compared, reported that ultrasonography had a sensitivity and specificity of 91% and 70%, respectively. Ultrasonography accurately predicted the presence and absence of packages in 39 of 45 suspects.…”
Section: Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation